Zadanie 1
9 - 7 = -2 4 - 7 = -3 0 - 7 = -7
10 - 7 = 3 1 - 7 = -6 (-10) - 7 = -17
Zadanie 2
a)
(-7) - 3 = (-7) + (-3) = -10
(-4) - 8 = (-4) + (-8) = -12
7 - 10 = 7 + (-10) = -3
9 - 11 = 9 + (-11) = -2
b)
4 - (-5) = 4 + 5 = 9
(-2) - (-3) = (-2) + 3 = 1
19 - (-9) = 19 + 9 = 28
(-1) - (-15) = (-1) + 15 = 14
Zadanie 3
8 - 3 = 8 + (-3) - D
(-3) - 8 = (-3) + (-8) - O
8 - 3 = 8 + (-3) - D
3 - 8 = 3 + (-8) - A
(-2) - (-6) = (-2) + 6 - W
3 - 8 = 3 + (-8) - A
(-6) - (-2) = (-6) + 2 - N
(-6) - 2 = (-6) + (-2) - I
8 - (-3) = 8 + 3 - E
Hasło: Dodawanie